Introduction to entrepreneurship - Hill, Lynne; O'Malia, Thomas J.; Quisic (firm) ([Los Angeles, Calif.] : Quisic, 2005)
Thomas O'Malia, the director of the Entrepreneurship Program, University of Southern California, discusses the myth that usually existed in entrepreneurship. Reviews the attitudes and skill sets necessary to launch an enterprise and considers the entrepreneurial lifecycle
Title from title screen
Executive produce, Brenda Reiswerg, Greg Ackerman, Tom Geniesse ; editor, Carrie Ansell
Presented by Professor Thomas J. O'Malia
Keywords: Entrepreneurship; New business enterprises; Management; Business planning